Optimasi Rantai Pasok Suku Cadang Kritis Perawatan Pesawat Terbang melalui Penerapan Prinsip Lean Manufacturing: Upaya Pengurangan Aircraft Maintenance Down Time di Area Line Maintenance - Mukhammad Yusuf Hakim; Zaenal Muttaqien; Ahmad Gustian Hendra Wijaya; Xaverus Johnstone Dapa Keti (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2026)
In the aircraft maintenance process, the timeliness of maintenance is a crucial factor. Given that aircraft are highly sophisticated modes of transportation, the numerous international regulations governing them, coupled with the high cost of aircraft spare parts, lead many airlines (air operators) to pay close attention to the maintenance of their aircraft at aircraft maintenance, repair, and overhaul (MRO) facilities. The availability of spare parts, maintenance support facilities, and their relationship to aircraft operations are key factors for airlines in conducting feasibility tests and evaluations of an aircraft maintenance facility (MRO). Lean Manufacturing is a system adapted from Japan that is considered highly beneficial for many companies, not only in the manufacturing sector but also increasingly in the aviation industry, particularly within aircraft maintenance processes. Many airlines have complained about the length of maintenance processes, which disrupt operations and can even lead to minor and major incidents. Keywords: Lean Manufacturing, Aircraft Maintenance, Supply Chain Management, Aviation Logistic.